Selective Methane Oxidation to Methanol on Cu-Oxo Dimers Stabilized by Zirconia Nodes of an NU-1000 Metal–Organic Framework - Zheng, Jian; Ye, Jingyun; Ortuño, Manuel A; Fulton, John L; Gutiérrez, Oliver Y; Camaioni, Donald M; Motkuri, Radha Kishan; Li, Zhanyong; Webber, Thomas E; Mehdi, B. Layla; Browning, Nigel D; Penn, R. Lee; et al. (Journal of the American Chemical Society, 2019)
Mononuclear and dinuclear copper species were synthesized at the nodes of an NU-1000 metal–organic framework (MOF) via cation exchange and subsequent oxidation at 200 °C in oxygen. Copper-exchanged MOFs are active for selectively converting methane to methanol at 150–200 °C. At 150 °C and 1 bar methane, approximately a third of the copper centers are involved in converting methane to methanol. Methanol productivity increased by 3–4-fold and selectivity increased from 70% to 90% by increasing the methane pressure from 1 to 40 bar. Density functional theory showed that reaction pathways on various copper sites are able to convert methane to methanol, the copper oxyl sites with much lower free energies of activation. Combining studies of the stoichiometric activity with characterization by in situ X-ray absorption spectroscopy and density functional theory, we conclude that dehydrated dinuclear copper oxyl sites formed after activation at 200 °C are responsible for the activity.